The Effects of Reading Habit and Vocabulary Mastery toward Student’s Reading Comprehension in Serang City - Riandi Riandi (Universitas Mathla'ul Anwar Banten, 2016)
This study aims to determine the effects of reading habit and vocabulary mastery toward student’s reading comprehension at Private Islamic Junior High Schools in Serang City –Banten. Research hypothesis included: 1) There are significant effects of reading habit and vocabulary mastery towards students’ reading comprehension, 2) There is a significant effect of reading habit towards students’ reading comprehension, 3) There is a significant effect of vocabulary mastery towards students’ reading comprehension.The method used in this research is a survey method. Sample was taken as many as 50 students with sample random technique. Data collected by test to the sample. Data analysis using descriptive statistics such as finding the mean, median, mode, standard deviation, and inferential statistics is to look for multiple regression by using ANOVA and coefficient table. This research was conducted from November until December 2014.The result of the research concluded:1) there are significant effects of reading habit and vocabulary mastery collaboratively towards students’ reading comprehension. It can be proved by F test = 4,255.and sig=0.004 <0.05, 2)there is a significant effect of the reading habit towards students’ reading comprehension. It can be proved by t test = 3,393, and sig=0.026<0.05, 3) there is a significant effect of the vocabulary mastery towards students’ reading comprehension. It can be proved by t test = 3,556 and sig=0.021<0.05.